2019
DOI: 10.1093/jamia/ocz095
|View full text |Cite
|
Sign up to set email alerts
|

Medication safety alert fatigue may be reduced via interaction design and clinical role tailoring: a systematic review

Abstract: Objective Alert fatigue limits the effectiveness of medication safety alerts, a type of computerized clinical decision support (CDS). Researchers have suggested alternative interactive designs, as well as tailoring alerts to clinical roles. As examples, alerts may be tiered to convey risk, and certain alerts may be sent to pharmacists. We aimed to evaluate which variants elicit less alert fatigue. Materials and Methods We sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
67
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 66 publications
0
67
0
1
Order By: Relevance
“…They also proposed tiering of alerts to improve acceptance and consideration of human factors in CDS design [20] The analytic reviews analyzed the features of previously implemented CDS tools. Several reviews examined alert use, generally finding acceptance rates to be low [21] and override rates to be high [22][23][24]. Hussain et al delved into why alerts are so commonly overridden and found that although interruptive alerts are the most common design, they are also the least accepted.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They also proposed tiering of alerts to improve acceptance and consideration of human factors in CDS design [20] The analytic reviews analyzed the features of previously implemented CDS tools. Several reviews examined alert use, generally finding acceptance rates to be low [21] and override rates to be high [22][23][24]. Hussain et al delved into why alerts are so commonly overridden and found that although interruptive alerts are the most common design, they are also the least accepted.…”
Section: Resultsmentioning
confidence: 99%
“…Hussain et al delved into why alerts are so commonly overridden and found that although interruptive alerts are the most common design, they are also the least accepted. The authors also found that role-tailoring alerts to pharmacists instead of physicians had improved acceptance [21]. Carli et al undertook a systematic review of positive predictive values (PPVs) of CDS alerts as a proxy for clinical relevance, finding massive PPV variations from 0% to 97%, with most in the 20%-40% range.…”
Section: Resultsmentioning
confidence: 99%
“…Modal dialogs are relatively easy to implement, and there seems to be a perception that modal dialogs-because of their interruptive nature-are an effective means of obtaining clinicians' attention, leading to a higher likelihood of actions. However, there has been an extensive body of literature suggesting that alerts delivered through modal dialogs are frequently overridden, 22,45 much like in our study, in which participants overrode 96% of modal dialogs. Further, modal dialogs are a significant contributing factor to clinician frustration, 46 burnout, 47 and potentially unsafe prescribing practices.…”
Section: Discussionmentioning
confidence: 48%
“…This approach is commonly referred to as microservice architecture [25].Specifying standard interfaces, CDS Hooks (https://cds-hooks.org), provides a hook-based pattern for automatically invoking CDSS functions within routine clinical workflows [26]. This specification natively supports HL7 FHIR R4 to simplify the data flow, enabling easy integration of HISs and CDSS services.The experience shows that most of the CDSSs are standalone implementations focused on one clinical condition or workflow [27][28][29]. However, the implementation of sophisticated clinical decision support platforms that are capable of providing a full spectrum of clinical decision support functionality to various medical information systems is still missing.…”
mentioning
confidence: 99%
“…The experience shows that most of the CDSSs are standalone implementations focused on one clinical condition or workflow [27][28][29]. However, the implementation of sophisticated clinical decision support platforms that are capable of providing a full spectrum of clinical decision support functionality to various medical information systems is still missing.…”
mentioning
confidence: 99%